2022
DOI: 10.1172/jci154833
|View full text |Cite
|
Sign up to set email alerts
|

Increasing on-treatment hepatocellular carcinoma risk with decreasing baseline viral load in HBeAg-positive chronic hepatitis B

Abstract: BACKGROUND It is unclear whether the level of serum hepatitis B virus (HBV) DNA at baseline affects the on-treatment risk of hepatocellular carcinoma (HCC) in hepatitis B e antigen–positive (HBeAg-positive), noncirrhotic patients with chronic hepatitis B (CHB). METHODS We conducted a multicenter cohort study including 2073 entecavir- or tenofovir-treated, HBeAg-positive, noncirrhotic adult CHB patients with baseline HBV DNA levels of 5.00 log 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 46 publications
(49 reference statements)
6
39
0
Order By: Relevance
“…Although the expansion of treatment criteria in CHB patients is highly controversial, 37 many Korean studies have suggested that expanding treatment indications may significantly reduce the incidence of HCC and mortality among those with CHB infection not currently eligible for treatment. [13][14][15][16][17][18]38 In fact, the results of this study are consistent with those of the previous global modelling studies, which suggested that scaling up the coverage of treatment to 80% of eligible individuals with CHB infection is essential to achieve a target of a 65% reduction in mortality by HBV. 39 While the risk of treatment-emergent adverse events is low, as the number of individuals treated increases, the absolute number of individuals experiencing treatment-emergent adverse events will also increase.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the expansion of treatment criteria in CHB patients is highly controversial, 37 many Korean studies have suggested that expanding treatment indications may significantly reduce the incidence of HCC and mortality among those with CHB infection not currently eligible for treatment. [13][14][15][16][17][18]38 In fact, the results of this study are consistent with those of the previous global modelling studies, which suggested that scaling up the coverage of treatment to 80% of eligible individuals with CHB infection is essential to achieve a target of a 65% reduction in mortality by HBV. 39 While the risk of treatment-emergent adverse events is low, as the number of individuals treated increases, the absolute number of individuals experiencing treatment-emergent adverse events will also increase.…”
Section: Discussionsupporting
confidence: 90%
“…These data suggest that the complexity and strictness of current guidelines in defining treatment eligibility is a serious challenge in accomplishing the WHO's target to eliminate HBV by 2030. Although the expansion of treatment criteria in CHB patients is highly controversial, 37 many Korean studies have suggested that expanding treatment indications may significantly reduce the incidence of HCC and mortality among those with CHB infection not currently eligible for treatment 13–18,38 . In fact, the results of this study are consistent with those of the previous global modelling studies, which suggested that scaling up the coverage of treatment to 80% of eligible individuals with CHB infection is essential to achieve a target of a 65% reduction in mortality by HBV 39 …”
Section: Discussionsupporting
confidence: 85%
“…The authors hypothesize that a decreasing but considerable viral load (e.g., 5–8 log10 IU/mL) may indicate the progressive damage of hepatocytes, clonal hepatocyte repopulation, and subsequent increased risk of HCC, compared to their peers that received early treatment with the same range of HBV DNA levels. They concluded that early initiation of antiviral treatment with a high viral load (≥8.00 log10 IU/mL) may maintain the lowest risk of HCC in those patients [ 44 ].…”
Section: The Risk Of Hepatocellular Carcinoma In Chronic Hepatitis Bmentioning
confidence: 99%
“…We read with great interest the article by Choi et al, which concluded that baseline HBV DNA level was inversely associated with on-treatment hepatocellular carcinoma (HCC) risk in HBeAg-positive, noncirrhotic, chronic hepatitis B (CHB) patients ( 1 ). Their findings are novel, but several issues deserve discussion.…”
Section: To the Editormentioning
confidence: 99%